Case Study: Online Continuing Education for New Librarians. Issue 3 (2nd October 2017) - Hendrix, Beth R.; McKeal, Alyse E.
ABSTRACT: Continuing education is vital for new librarians to gain skills and knowledge beyond library school. Professional development offered free in an online environment is often the best option for staying current on the issues and trends necessary for young librarians to grow and flourish. This paper presents a case study of an online professional development series for new librarians implemented by the Online Programs Committee of the American Library Association's New Members Round Table.